Time and Tide Wait for No Man: A Response to Warwick Anderson and Michael M. J. Fischer. Issue 4 (1st December 2018) - Duara, Prasenjit
Abstract: The two leading scholars of EASTS reflect on two approaches of STS studies in East Asia and Southeast Asia: one that discusses the reactions, reflections, and recreations of scientific interventions and the other that looks for more strictly scientific contributions. I propose a third methodology that compares historical processes with oceanic flows. Scientific breakthroughs and attendant practices and emergences circulate beyond their controlling agents to interact with other currents and forces beyond their initial space-time horizons. They merge, converge, submerge, reemerge, create countercurrents, upwell, and return in other forms. Agency is important but deeply limited in historical processes. The ocean-atmosphere-land flows are both metaphorical and material. As material, they condition life and history on earth. The question that arises today is the extent to which the Anthropocene, an era where human activity represents the greatest influence on climate and the environment, will ravage the ocean and the degree to which the ocean will avenge our depredations. The social and historical study of science could do worse than track these flows and exchanges.